Triple diffusive convection of a non-newtonian fluid under the combined effect of compressibility and variable gravity - Aggarwal, Amrish; Dixit, Dhruva (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, triple diffusive convection in a Rivlin-Ericksen fluid layer, which is permeated with suspended particles in the porous medium under the effect of compressibility and variable gravity, is investigated. Linear stability theory and normal mode analysis have been used to study the problem under consideration. It is observed that, for stationary convection, suspended particles, compressibility and medium permeability have destabilizing/stabilizing effects under certain conditions. The variable gravity parameter destabilizes the system whereas stable solute gradients have a stabilizing effect.
Keywords: triple diffusion; Rivlin-Ericksen fluid; suspended particles; porous medium; compressibility; variable gravity